Polyacrylonitrile Nanofiber Composites as Efficient Removal of Pollutants for Wastewater: A Review Article - Al-Dulaimy, Zainab Abbas; Khalaf, Husam Saleem; Jadoo, Shaimaa Abdul Hussein; Fendi, Wedad J.; Waheed, Enass J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Polyacrylonitrile nanofiber (PANFS), a well-known polymers, has been extensively employed in the manufacturing of carbon nanofibers (CNFS), which have recently gained substantial attention due to their excellent features, such as spinnability, environmental friendliness, and commercial feasibility. Because of their high carbon yield and versatility in tailoring the final CNFS structure, In addition to the simple formation of ladder structures through nitrile polymerization to yield stable products, CNFS and PAN have been the focus of extensive research as potential production precursors. For instance, the development of biomedical and high-performance composites has now become achievable. PAN homopolymer or PAN-based precursor copolymer can be employed to make CNFS. Water gets polluted because it throws industrial waste bodies of water, especially those containing dyes, heavy metals, and inorganic and organic wastes. Adsorbents, which are cheap and readily available, can be used to address the issue of water deterioration. According to this review, numerous PAN variations are being employed in scientific and technological settings. Nanocomposite fibers need extensive research efforts to advance technology and bring them to commercialization.